Environmental role of wetlands in headwaters - NATO Advanced Research Workshop on the Environmental Role of Wetlands (NATO science series)
Internationally, the wetlands of headwater and upland regions provide many valuable environmental services. This book moves towards a more comprehensive inventory of the benefits and costs of headwater wetlands. It evaluates the research that tries to understand the tolerances, exchanges, checks and balances within headwater landscapes and the downstream impacts of changes in wetlands. It employs case studies and reviews from 21 nations spanning Europe, Africa, Asia and the Americas. It explores the new policy frameworks, changes in land husbandry, new systems for community education, participatory processes and technological interventions required for the effective management of headwater wetlands and the full integration of wetlands (including newly constructed wetlands) into environmental management and planning. In the past, most research dealt with wetlands as isolated features, this book examines wetlands in their watershed management context. Headwater wetlands -- Mapping wetlands in european headwater areas -- The role of forest on the hydrology of headwater wetlands -- Role of grassland ecosystems in protection of forested wetlands -- The effect of peat land drainage and afforestation on runoff dynamics -- Impact of herbaceous vegetation on recovery of a harvested headwater catchment -- Leaching of nitrogen from upland forest-regeneration sites into wetland areas -- Hydrology of disturbed peat-land, heads of the valleys, Wales -- Estimation of water budget in the forested peat-lands of western ireland -- Role of the planktonic communities in the regulation and indication of eutrofication processes in shallow mountain wetlands -- New wetland formation in subsidence hollows of western dondass, Ukraine -- Integrating wetlands into watershed management: effectiveness of constructed wetlands to reduce impacts from urban stormwater -- Disasters and climate change - their relation with wetland headwaters -- The alleghe lake (Dolomites, Italy): environmental role and sediment management -- Alpine wetlands from ecological network to land-based risk prevention -- Headwater resources and headwater hazards: perspectives from environmental education -- Hydrology of wetlands in the headwaters of great african rivers -- Headwater wetlands in eastern and Southern Africa -- Economic contribution of headwater wetlands -- The lake kinneret drainage basin -- Environmental change in headwater peat wetlands, UK -- Environmental problems of headwater wetlands in Hhungary -- Headwater wetlands in the Czech Republic -- Analysis of the water balance of small páramo catchments in south Ecuador -- Summary reports -- Headwater and wetland protection -- Next generation of watershed management programmes -- Conclusion – Wetlands in context -- Erratum.